Ant composition and activity patterns as determined by pitfall trapping and other methods in three habitats in the semi-arid Karoo - Lindsey, P.A.; Skinner, J.D. (Journal of arid environments, 2001)
The diversity and abundance of epigaeic ant species were determined across three habitats (riverine areas, gently sloping grassland areas and steep slope areas) in summer (November–December) and winter (May–June) of 1998 at Tussen die Riviere Nature Reserve in the Karoo, to determine temporal and spatial variations in the availability of potential prey species of the aardvark (Orycteropus afer). Pitfall trapping, dig sampling and quadrat sampling were used to ensure as complete a sampling effort as possible. Forty-five ant species of five sub-families and 17 genera were recorded. The grassland habitat yielded the highest abundance and diversity, followed by the steep slope and riverine areas. Ant abundance and diversity were higher during summer than winter in all three habitats. Anoplolepis custodiens was the most abundant species in summer, whilst Monomorium albopilosum was the most abundant species in winter. Pitfall trapping was responsible for recording more species than dig sampling or quadrat sampling. No method recorded all of the species present.